Metabolismo energético e termorregulação do tucano-toco (Ramphastos toco) - Chaves, Jussara Nascimento [UNESP] (2015)
Body temperature regulation in endotherms involves adjustments in heat exchange rates between the animal and the environment. One of those mechanisms include the modulation of the surface temperature of specific areas of the body through vasomotor adjustment promoting dissipation or conservation of body heat. This thermoregulatory adjustment is essential for maintenance of body temperature over a moderate temperature range, known as thermal neutral zone (TNZ), without increasing the metabolic rate (MR). Thermal windows are body regions poorly insulated and highly vascularized that are particularly efficient for heat dissipation through that mechanism. The beak of the toco-toucan (Ramphastos toco) was described as a highly efficient thermal window, assisting the thermal homeostasis of this bird. Therefore, is possible that the heat exchange adjustments through the beak have an important role on delimitation of TNZ. Hence, our goal in this study was to determinate the contribution of heat exchanges through de beak of R. toco on the amplitude and limits (lower and upper) of TNZ. For that, we measured metabolic rate, through oxygen consumption, over a range of ambient temperature from 0 to 35°C (every 5°C). MR measurements were made in birds with the beak intact (control group) and subsequently with the beak artificially insulated (experimental group). The limits of TNZ, 9.5-25.0°C for the control group and 10.8-23.3°C for the experimental group, did not differ between the treatments. MR differed among treatments only at elevated temperatures (30 and 35°C), reaching values of 0.97 mlO2.g -1.h-1 (± 0.06) for the control group and 1.20 mlO2.g -1.h-1 (± 0.07) for the experimental group at 35°C. These results indicate that under high temperatures, the insulation of the beak compromised the heat exchange with the environment, so the MR increased above normal to dissipate ... (Complete abstract click electronic access below)